A plastic damage constitutive model for rock-like material focusing on the hydrostatic pressure induced damage and the interaction of tensile and shear damages under impact and blast loads. (October 2022) - Shu, Yun; Zhu, Zheming; Wang, Meng; Ying, Peng; Wang, Fei; Wan, Duanying; Li, Xiaohan; Gao, Weiting
Abstract: Although many mechanical responses of rock-like material subjected to dynamic loads can be simulated by commonly-used material models, it's still hard to accurately describe the interactive mechanism of tensile and shear damages caused by different kinds of loads. This paper presents a novel constitutive model with three smooth failure strength surfaces and three invariants. The new model can precisely and quantitatively capture the damage mechanisms of hydrostatic pressure based on test data and the interaction of the tensile and shear damages based on the Mohr-Coulomb criterion. Then, the new model is implemented into LS-DYNA, and a series of numerical validations, e.g. TXC, UUC, and UUT tests at single element, SHPB tests, rock blast test, and projectile penetration, are conducted. A satisfactory agreement between the numerical predictions and experimental data shows the suitability and accuracy of the present model for rock-like material under dynamic impact and blast loads.